Kinetic Studies of the Form of Substrate Bound by Phosphoenolpyruvate Carboxylase - Wedding, Randolph T. (1988)
Phosphoenolpyruvate carboxylase isolated from maize (Zea mays L.) leaves was assayed with varying concentrations of free phosphoenolpyruvate at several fixed-varying concentrations of free magnesium higher than required to saturate the enzyme reaction. These assays produced velocity data which were found to form a family of individual lines when plotted against free phosphoenolpyruvate or against total phosphoenolpyruvate, but not when plotted against the concentration of the complex of phosphoenolpyruvate with magnesium. In this latter case, the points from all the fixed-varying concentrations fell on the same line, which can be fitted to a modified Michaelis-Menten equation with a multiple correlation coefficient R(2) = 0.995. Similar results were obtained when the enzyme from the C(4) plant maize was assayed with manganese rather than magnesium and when phosphoenolpyruvate carboxylase from leaves of the C(3) plant wheat (Triticum vulgare Vill.) was assayed with magnesium. However, at pH 7.0 the enzyme from the Crassulacean acid metabolism plant Crassula argentea did not produce a satisfactory single line when plotted against the complex of metal ion and substrate, but did so when the assay pH was raised to 8.0. It is concluded that in general the preferred form of substrate for phosphoenolpyruvate carboxylase is the complex of phosphoenolpyruvate with the metal ion.